Key indicators for Asia and the Pacific 2017 (Asian Development Bank, 2017)
The Key Indicators presents the latest statistics on a comprehensive set of economic, financial, social, environmental, and Sustainable Development Goal (SDG) indicators for the 48 regional members of the Asian Development Bank. It is designed to serve as a resource for information on development issues across the region for a wide audience, including policy makers, development practitioners, government officials, researchers, students, and the general public.A key component of this years report is a summary of findings from three pilot household surveys to support the development of standardized methods and guidelines for collecting sexdisaggregated data on asset ownership.